Traditional Range Of Maanta Marapulai In Jorong Pauh, Matur District, Agam District - Ilham, Rofika; Syarif, Wirnelis (Universitas Negeri Padang, 2023)
This study to describe types of equipment and food served at the Maanta Marapulai event in Jorong Pauh, Matur District, Agam Regency. This study used qualitative research methods. Data sources were obtained from the secretary of the wali nagari, ninik mamak, bundo kanduang, traditional leaders of Cadiak clever and Bijo Pari as well as people who know about the Maanta Marapulai event in Jorong Pauh, Matur sub-district, Agam district.The data obtained from the field will be analyzed by means of data reduction, data presentation and drawing conclusions. The results of the study: 1) the series of events were carried out by Baarak during the day, 2) types of traditional food, namely: Samba Bajamba (rendang, Kalio chicken, sweet potato crackers and salted fish) and Drinking Kawa Bajamba (lamang, diamonds). , galamai, klepon, pinyaram) 3) equipment used by Katidiang Gadang, Katidiang Bujang, Katidiang ketek, Carano 4) equipment used in Rice, Crackers, Banana, Betel, Corn, Salt, Chili, Raw Salted Fish, Cooking Oil, Blanket , Marapulai clothes 5) the meaning contained in the Maanta Marapulai event is to deliver Marapulai to Anak Daro's house in a good way and be provided with provisions to start married life 6) the food served has meaning, Samba Bajamba which means Tigo Sapilin rope (Sipokok, Bako, Sumando), Drink Kawa Bajamba which means there is a word of consensus and respect for Ninik Mamak. Keywords: Maanta Marapulai Event, Equipment, Traditional Food, Matur